Assessment of the Ecological and Geographical Condition of the Basin System Lakes Strilske (Hydrological Monument of Nature) - Martyniuk V. О.; Andriichuk , S. V. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2021)
Topicality. The available information on specific lakes of nature protection fund (NPF) objects, primarily of local significance, is limited to brief information on morphometric and hydrological characteristics, information on the rare component of aquatic organisms and the species diversity of the adjacent catchment areas. This state of affairs does not benefit the development of protected areas and encourages ecological and geographical searches of lakes or lake-basin systems, which are part of the NPF. Purpose is to assess the ecological and geographical condition of the lake basin system Strelske (hydrological monument of nature) for cadastral needs of NPF objects of Polissya region of Ukraine. Methods of regional constructive-geographical limnology, landscape-limnological analysis, soil-geochemical profiling of lake catchments, GIS-cartographic modeling. Results of the study are presented in the form of a cartographic model of the spatial-typological structure of the lands of the lake catchment. Shooting and substantiation of its geoecological condition, bathymetric map of the lake and morphological-morphometric and hydrological calculations of the LBS. The hydrochemical parameters of the lake were analyzed according to the block of indicators of salt composition, tropho-saprobiological characteristics and substances of toxic action. The lithological composition and capacity of the bottom sediments of the lake are estimated, the graphs of radial migration of chemical elements and compounds at one of the probing points are constructed and the qualitative composition of the lake sapropel is substantiated. Using GIS technologies, a landscape map of the natural-aqual complex of the lake was built. Shooting and landscape-metometric assessment of its morphological structure. Conclusions. The basin system has in the past undergone anthropogenic transformations as a result of reclamation nature management, which has limited the share of surface runoff into the lake. The lake water exceeded the MPC by 1.7 times the chemical oxygen demand, 1.6 times the biological oxygen demand and 2 times the total iron consumption. The lake basin is 65.7% filled with bottom sediments, which are represented mainly by organo-iron sapropel. The littoral aqua facies of the lake suffer the greatest anthropogenic load, which is connected with the recreational activities of the seasonally functioning recreation center.